Fuzzy hybrid computing in construction engineering and management : theory and applications - Robinson Fayek, Aminah (Emerald Publishing Limited, 2018)
This book provides an introduction to fuzzy logic and surveys the latest research and state-of-the-art applications in fuzzy hybrid techniques. Authors cover several methodologies in the theory and implementation of fuzzy hybrid computing, including fuzzy arithmetic, fuzzy hybrid optimization, fuzzy hybrid machine learning, fuzzy multi-criteria decision-making, fuzzy simulation, fuzzy cognitive maps, and fuzzy data modeling. The book presents several practical applications of these techniques to solve real-world problems in a wide range of construction engineering and management problems. The construction industry is a vital part of many national economies, and its performance is largely dependent on the effective planning, execution, and control of construction projects. The completion of these construction processes is, in turn, often dependent on numerous interacting factors and human activities, both of which introduce vagueness and subjective uncertainty into these already complex processes. Expert knowledge, expressed in linguistic terms, is often essential for effective decision-making. Fuzzy logic, which has applications in many engineering disciplines, has the potential to address some of the challenges inherent in construction engineering and management, in part because of its strengths in dealing with subjective uncertainty, modeling human reasoning, and computing with linguistic terms. However, fuzzy logic alone has a number of limitations that can only be overcome by integrating it with other techniques that have complementary strengths, thus leading to advanced and powerful fuzzy hybrid computing techniques. This book is of particular interest to students, researchers, and practitioners interested in the latest developments in fuzzy hybrid computing in construction engineering and management.